Phonon Transmission Across Silicon Grain Boundaries by Atomistic Green's Function Method - Li, Chen; Tian, Zhiting (Frontiers in Physics, 2019)
Nanostructured materials are of great interest for many applications because of their special properties. Understanding the effect of grain boundaries on phonon transport in polycrystals is important for engineering nanomaterials with desired thermal transport properties. The phonon transport properties of Σ3 grain boundaries in silicon are investigated by employing atomistic Green’s function method. Results show that similar to electron transport, the perfect grain boundary does not significantly reduce the thermal conductance, while defective grain boundaries can dramatically reduce the thermal conductance. This work may be helpful for the understanding of the underlying thermal transport mechanism with grain boundaries and the design of grain boundaries for energy applications.